PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR PERTANIAN - Caroline Thesman (Business Accounting Review, 2014)
Family firms are still dominating in Indonesia, where previous studies on the influence of the family companies to profitability and value of the company showed different results that refer to inconsistencies . This study aimed to examine the affect of family control on the profitability and value of the company . Profitability measured by using ROA and firm’s value by using Tobin 's Q. Control variables used were  firm size , sales growth , and leverage . The sample used in this study was the agricultural industry companies that meet certain criteria and were analyzed by using multiple linear regression . The results of this study proved that the family control and leverage negatively affected profitability , sales growth positively affected on profitability , and firm size had no affected on profitability. On the other hand  family control and sales growth had no affect on firm’s value , only firm size and leverage negatively affected the value of the company.